2013
DOI: 10.1097/hjh.0b013e328362bad7
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension-related diseases as a common cause of hospital mortality in Tanzania

Abstract: Objective Hypertension is believed to be an increasingly common driver of the epidemic of non-communicable diseases (NCDs) in sub-Saharan Africa, but prospective data are scarce. The objective of this prospective study was to determine the contribution of hypertension to deaths, admissions, and hospital days at a Tanzanian zonal hospital. Methods: Between 2009 and 2011, diagnoses were recorded for all medical admissions together with age, gender, length of hospitalization and in-hospital mortality. Results A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 24 publications
2
53
1
Order By: Relevance
“…Since December 2008, our hospital has used a standard list of recommended discharge diagnoses. 1 These diagnoses were adapted from the WHO’s International Classification of Diseases version 10 (ICD-10). 17 This standard list includes all of the diagnoses reported in this study, as in our prior work.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since December 2008, our hospital has used a standard list of recommended discharge diagnoses. 1 These diagnoses were adapted from the WHO’s International Classification of Diseases version 10 (ICD-10). 17 This standard list includes all of the diagnoses reported in this study, as in our prior work.…”
Section: Methodsmentioning
confidence: 99%
“…1,2 Therefore, hospitals may offer an important window of opportunity to identify these conditions, initiate treatment and link to primary care. 3,4 Unfortunately, little is known about post-hospital outcomes for African adults.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of stroke in adults aged 30-69 in Tanzania is one of the highest rates in the world (120/100,000 person years) and is 6-10 fold higher than the US, UK and Canada [11]. At our own hospital in Western Tanzania, HTN-related diseases accounted for 15% of all medical admissions, deaths, and hospital days – second only to HIV – and half of these deaths occurred in adults < 65 years old [12]. The early onset of HTN-related complications has been attributed to low rates of diagnosis, treatment and control [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…27 For example, a recent study in Tanzania revealed that noncommunicable diseases were responsible for only 27 percent of the country's health burden but for nearly half of its hospital admissions and hospitalization days. 28 Studies conducted in the United States and New Zealand showed higher rates of inpatient surgical procedures for the treatment of noncommunicable diseases than for that of communicable, maternal, and neonatal diseases (34 percent versus 24 percent in the United States and 32 percent versus 16 percent in New Zealand). 29,30 Late diagnosis of many cases of cancer, diabetes, and cardiovascular disease in low-income nations increases the demand for inpatient surgical procedures.…”
mentioning
confidence: 99%